(Ce, Gd):YAG-Al2O3 composite ceramics for high-brightness yellow light-emitting diode applications. Issue 3 (March 2022) - Li, Xiaoyun; Chen, Jian; Liu, Zhuguang; Deng, Zhonghua; Huang, Qiufeng; Huang, Jiquan; Guo, Wang
Abstract: (Ce, Gd):YAG-Al2 O3 composite ceramics were prepared for high-brightness yellow LED (565−590 nm) applications. Phase fraction, microstructure, thermal quenching effect, and luminescent properties of composite ceramics with varying compositions were studied in detail. Collaborating composite ceramics with InGaN blue chips, the relationship between thermal conductivity, temperature rise during LED-driven phosphor conversion, and steady-state luminous efficiency were elucidated. As the proportion of Al2 O3 increases from 0 to 40 wt%, the steady-state luminous efficiency of yellow LED is enhanced from 100.88–109.49 lm W −1, benefiting from the increased thermal stability and reduced operating temperature of ceramics (from 141.1–132.2 °C). Additionally, scattering behavior and extraction efficiency of composite ceramics with different thicknesses were investigated.